Analisis Pemahaman dan Problematika Kelas XII ‎ SMK Dr Indra Adnan Indragiri College tentang Hukum Waris Islam - Aliefia Qatrunnada; Herdawati; Herdiansyah (Jurnal Indragiri Penelitian Multidisiplin, 2022)
In writing this journal, the author uses the empirical legal research method in which the data collection process is carried out in the form of a survey by conducting a questionnaire or questionnaire technique where the author sends a Google Form link to class XII students at SMK Dr. Indra Adnan Indragiri College to be filled in by the respondent. In terms of learning Islamic inheritance law, basically at the high school or vocational school level, it is a subject that is quite difficult for students and even university students. As happened to students of class XII SMK Dr. Indra Adnan Indragiri College where there are still many of these students who do not understand Islamic inheritance law. This is because the material is quite complicated and also in inheritance law there are calculations and provisions that apply to be able to calculate each part in a particular case so that this is what makes it difficult for the majority of students to understand. If it's only material without counting students and female students, of course many understand and understand about these roses, but if it is related to mathematics, of course this becomes a complicated matter and must be studied carefully. So that in this case there are problems in terms of studying rosemary science among high schools, where the problems and problems can come from the teacher, the students themselves, as well as the learning strategies and models applied in each school.